1992
DOI: 10.4153/cmb-1992-052-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Residual Finiteness of Polygonal Products of Nilpotent Groups

Abstract: In general polygonal products of finitely generated torsion-free nilpotent groups amalgamating cyclic subgroups need not be residually finite. In this paper we prove that polygonal products of finitely generated torsion-free nilpotent groups amalgamating maximal cyclic subgroups such that the amalgamated cycles generate an isolated subgroup in the vertex group containing them, are residually finite. We also prove that, for finitely generated torsion-free nilpotent groups, if the subgroups generated by the amal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…Finally, we apply our result to a special kind of generalized free products, known as polygonal products of groups, and we generalize some results found in [2], [11].…”
Section: Letg-e * H F Suppose That (A) E and F Are N C And H-separabsupporting
confidence: 65%
“…Finally, we apply our result to a special kind of generalized free products, known as polygonal products of groups, and we generalize some results found in [2], [11].…”
Section: Letg-e * H F Suppose That (A) E and F Are N C And H-separabsupporting
confidence: 65%
“…The proofs of next two results are very similar to Lemma 4.5 and Theorem 4.6 in [8]. Here we use Z i (G) to denote the i-th term of the upper central series of G with Z 1 (G), the center of G.…”
Section: Preliminariesmentioning
confidence: 57%
“…And they gave an example of a polygonal product of finitely generated nilpotent -or free-groups which is not RF . However, in [6,8], Tang and Kim showed that certain polygonal products of finitely generated nilpotent groups are RF or π c . Then, Allenby [1] constructed polygonal products of nilpotent groups which are not RF , hence untidy conditions in [8] can not be removed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [3], Allenby and Tang proved that polygonal products of four finitely generated free abelian groups, amalgamating cyclic subgroups with trivial intersections, is residually finite. Kim and Tang [9] showed that certain polygonal products of four nilpotent groups, amalgamating cyclic subgroups with trivial intersections, are residually finite. In this paper, we prove that polygonal products of more than four polycyclic-by-finite groups amalgamating any subgroups, contained in the centres of their vertex groups, with trivial intersections are 7r c (Theorem 2.11), hence they are residually finite.…”
Section: Introductionmentioning
confidence: 99%